Pengaruh Rotasi Auditor Dan Workload Terhadap Kualitas Audit - Marlina (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2025)
This research seeks to examine the effects of auditor rotation and workload on the quality of audits. The study population comprises manufacturing firms listed on the Indonesia Stock Exchange from 2020 to 2023. This research utilizes a quantitative methodology, with sample selection executed by purposive sampling. The data for this study were derived from audited financial reports of firms listed on the Indonesia Stock Exchange, received from the official website of the stock exchange in Indonesia. The data were examined by multiple linear regression analysis. The results demonstrate that workload adversely influences audit quality, but auditor rotation has no substantial effect on audit quality.